Designing fit-for-purpose indicators to connect nature and people’s well-being in New Zealand - Ausseil, Anne-Gaelle Elsa; Booth, Pamela; Greenhalgh, Suzie; Samarasinghe, Oshadhi; Collins, Alison (Frontiers in Environmental Science, 2023)
Recognizing the value of nature for people's well-being is key to ensuring protection of the environment for current and future generations. However, data to demonstrate the connection between nature and well-being, areis needed for environmental reporting, to inform policy development and evaluate progress toward outcomes. While many indicators exist, they are mostly derived from available data collected for other purposes and there is limited, if any, description of how these indicators were designed. Based on a conceptualization of nature-well-being connections, we propose a participatory process to identify fit-for-purpose indicators linking nature to human well-being. The process uses a series of targeted questions to explore how different aspects of well-being rely on nature, enabling more fitting indicators to be identified by the participatory group. The process was refined and tested in workshops with stakeholders in a New Zealand context.